2016
DOI: 10.3126/jcmsn.v12i3.16012
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of nursing students on Hospital Acquired Infections in Western region of Nepal

Abstract: Background & Objectives: Hospital-acquired infections (HAIs) are a common problem and challenge faced by hospitals in all countries around the world. Nurses are an important part of the healthcare team that plays a unique role in the control of HAIs. Compliance on the part of healthcare workers (HCWs) including nurses with standard precautions has been recognized as being an efficient means to prevent and control HAIs. The present study was conducted with objective of understanding the level of Knowledge, atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
2
13
0
2
Order By: Relevance
“…A similar result was also noted in a recent study involving Nepalese students (Paudel et al. ). Utilizing the Hand Hygiene Knowledge Questionnaire for Health Care Workers (HHKQHCW) by the WHO, the majority or 84% of the nursing students had scored lower than 75% of the total score.…”
Section: Hand Hygiene Knowledgesupporting
confidence: 90%
See 2 more Smart Citations
“…A similar result was also noted in a recent study involving Nepalese students (Paudel et al. ). Utilizing the Hand Hygiene Knowledge Questionnaire for Health Care Workers (HHKQHCW) by the WHO, the majority or 84% of the nursing students had scored lower than 75% of the total score.…”
Section: Hand Hygiene Knowledgesupporting
confidence: 90%
“…; Paudel et al. ). Other studies explored predictive factors of HH compliance (Cruz & Bashtawi ; Foote & El‐Masri ; Hernández‐García & Cardoso ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The main reasons for this may be lack of infrastructures, lack of trained manpower and lack of awareness about the importance of hand hygiene. 18 Further, local hand hygiene compliance data are not available. So, in this scenario this study will be a wakeup call for the responsible authorities to implement the hand hygiene programs in hospitals of Nepal.…”
Section: Resultsmentioning
confidence: 99%
“…A study in Nepal described that the lack of role models for infection control and formal training of HH could be considered as possible barriers to apply correct HH measures 25 . Accordingly, throughout our study, it was found that students' practice of HH was affected by the performance of their role models which was comparable to the findings of Hamadah et al in which they stated that students lack proper HH practice in the absence of living examples (physicians, residents) 6 .…”
mentioning
confidence: 99%